Cybersecurity Description and Control Criteria to Strengthen Corporate Governance - Grove, Hugh; Clouse, Mac; Schaffner, Laura Georg (Journal of Leadership, Accountability and Ethics, 2019)
The dangers of not properly focusing upon cybersecurity risks were emphasized by recent, notorious attack and hack examples. With guidance from key sources, like the AICPA Cybersecurity Guide, cybersecurity strategies can be developed by corporate executives and Board of Directors to help thwart such attacks. An immediate trend for data security is the General Data Protection Regulation adopted by the European Union in 2018 as well as quantum computing. If all of this is accomplished, the entity’s corporate governance would be strengthened by corporate executives and Boards of Directors who are the key gatekeepers for protecting and enhancing the investments of company stakeholders.